Multi-objective drilling parameter optimization of hybrid metal matrix composites using grey relational analysis. (2021) - Udaya Prakash, J.; Sarala Rubi, C.; Rajkumar, C.; Jebarose Juliyana, S.
Abstract: The aim of this research work is to investigate the effect of the process parameters on the thrust force and burr height during the drilling of hybrid metal matrix composites. Stir casting was used to manufacture hybrid MMCs. Fly ash and boron carbide were the reinforcements used in the manufacture. Tests were carried out in a computer-controlled vertical machining center together with a cutting tool dynamometer to measure the thrust power. The experiments were conducted based on a L27 orthogonal array. Multi-response optimization was performed using grey relational analysis for obtaining minimum thrust force and minimum burr height. The optimum level of input factors namely feed, spindle speed, drill material and reinforcement percentage was defined for low thrust force and low burr height. Confirmation experiments showed that the drilling parameters in the drilling of hybrid metal matrix composites are precisely optimized.